Cold Conditioned: Discovery of Novel Alleles for Low-Temperature Tolerance in the Vavilov Barley Collection - Sallam, Ahmad H.; Smith, Kevin P.; Hu, Gongshe; Sherman, Jamie; Baenziger, Peter Stephen; Wiersma, Jochum; Duley, Carl; Stockinger, Eric J.; Sorrells, Mark E.; Szinyei, Tamas; Loskutov, Igor G.; Kovaleva, Olga N.; et al. (Frontiers in Plant Science, 2021)
Climate changes leading to higher summer temperatures can adversely affect cool season crops like spring barley. In the Upper Midwest region of the US, one option for escaping this stress factor is to plant winter or facultative type cultivars that can be sown in autumn and harvested in early summer before the onset of high temperature stress. However, the major challenge in breeding such cultivars is incorporating sufficient winter hardiness to survive the extremely low temperatures that commonly occur in this production region. To broaden the genetic base for winter hardiness in the University of Minnesota breeding program, 2,214 accessions from the N. I. Vavilov Institute of Plant Industry (VIR) were evaluated for winter survival (WS) in St. Paul, Minnesota. From this field trial, 267 (>12%) accessions survived (designated as the VIR-LTT [low temperature tolerant] panel) and were subsequently evaluated for WS across six northern and central Great Plains states. The VIR-LTT panel was genotyped with the Illumina 9K SNP chip and then a genome-wide association study was performed on seven WS datasets. Twelve significant associations for WS were identified, including the previously reported frost resistance gene FR-H2 as well as several novel ones. Multi-allelic haplotype analysis revealed the most favorable alleles for WS in the VIR-LTT panel as well as another recently studied panel (CAP-LTT). Seventy-eight accessions from the VIR-LTT panel exhibited a high and consistent level of WS and are being used in several winter barley breeding programs in the US and in a multiparent population.